Dandy-Walker Malformation, Mega Cisterna Magna - Mudritskiy, Valentin; Dykky, M.; Pereira, D. (Portuguese Journal Internal Medicine, 2016)
We present a 38 years oldmale patient who was admitted to the Emergency Room for sudden vertigo onset. His personal history revealed several episodes of dizziness. The CT scan shows hypodense area, cerebellar median suggesting mega cisterna magna.